Full stack development with Spring Boot and React : build modern and scalable full stack applications using the power of Spring Boot and React - Hinkula, Juha (Packt Publishing, 2022)
Getting started with full stack development can be daunting. Even developers who are familiar with the best tools, such as Spring Boot and React, can struggle to nail the basics, let alone master the more advanced elements. If you're one of these developers, this comprehensive guide covers everything you need! This updated edition of the Full Stack Development with Spring Boot 2 and React book will take you from novice to proficient in this expansive domain. Taking a practical approach, this book will first walk you through the latest Spring Boot features for creating a robust backend, covering everything from setting up the environment and dependency injection to security and testing. Once this has been covered, you'll advance to React frontend programming. If you've ever wondered about custom Hooks, third-party components, and MUI, this book will demystify all that and much more. You'll explore everything that goes into developing, testing, securing, and deploying your applications using all the latest tools from Spring Boot, React, and other cutting-edge technologies. By the end of this book, you'll not only have learned the theory of building modern full stack applications but also have developed valuable skills that add value in any setting.